2019
DOI: 10.1186/s13568-019-0810-9
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of E. coli phage ZCEC5 in chitosan–alginate beads as a delivery system in phage therapy

Abstract: Bacteriophages can be used successfully to treat pathogenic bacteria in the food chain including zoonotic pathogens that colonize the intestines of farm animals. However, harsh gastric conditions of low pH and digestive enzyme activities affect phage viability, and accordingly reduce their effectiveness. We report the development of a natural protective barrier suitable for oral administration to farm animals that confers acid stability before functional release of bead-encapsulated phages. Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 48 publications
2
52
1
Order By: Relevance
“…Most of encapsulation strategies reported for phages were driven by the need to protect them from the adverse conditions found in the digestive tract, such as the low pH and the activity of enzymes. In this context, phages have been encapsulated mostly in alginate-based microspheres (Abdelsattar, Abdelrahman, Dawoud, Connerton, & El-Shibiny, 2019;Colom et al, 2017;Moghtader, Eğri, & Piskin, 2017) and liposomes (Otero et al, 2019). More recently, studies have reported phages encapsulation to be further applied in food products.…”
Section: Introductionmentioning
confidence: 99%
“…Most of encapsulation strategies reported for phages were driven by the need to protect them from the adverse conditions found in the digestive tract, such as the low pH and the activity of enzymes. In this context, phages have been encapsulated mostly in alginate-based microspheres (Abdelsattar, Abdelrahman, Dawoud, Connerton, & El-Shibiny, 2019;Colom et al, 2017;Moghtader, Eğri, & Piskin, 2017) and liposomes (Otero et al, 2019). More recently, studies have reported phages encapsulation to be further applied in food products.…”
Section: Introductionmentioning
confidence: 99%
“…As was shown by Międzybrodzki et al, only a small fraction (<0.1%) of oral administered phage was observed in the intestines, even after neutralizing antacid administration. The rationale behind several reviewed studies is to overcome such problems by protecting bacteriophages against harmful environments through embedding in a biomaterial matrix (Kim et al, 2015;Moghtader et al, 2017;Abdelsattar et al, 2019;Otero et al, 2019;Vinner et al, 2019).…”
Section: Advantages Of Bacteriophage Loaded Biomaterials For Local Dementioning
confidence: 99%
“…The presence of organic solvents and their volatility were also observed to be detrimental to phage activity (Salalha et al, 2006). Because of these practical limitations in applying organic solvents, water-soluble biopolymers such as sodium alginate are frequently used for bacteriophage encapsulation (Kim et al, 2015;Abdelsattar et al, 2019;Alves et al, 2019). Agarwal et al (2018) could also prevent exposure of phages to organic solvents by adding them on poly(lactide-co-glycolic acid) (PLGA) porous microspheres, which allowed the phage to be directly absorbed.…”
Section: Considerations In Manufacturing Bacteriophage Loaded Biomatementioning
confidence: 99%
See 2 more Smart Citations